Ethics and spiritual care : a guide for pastors, chaplains, and spiritual directors - Lebacqz, Karen, 1945-; Driskill, Joseph D. (Nashville, Abingdon Press, 2000)
"Recent years have seen escalating numbers of allegations that pastors and other spiritual guides have misused their office by providing damaging, and even abusive, spiritual care to those in their charge. Observing this trend, Karen Lebacqz and Joseph D. Driskill were moved to ask certain questions: What constitutes good spiritual care? When it comes to caring for the "spirits" of the people they work with, what are the basic ethical obligations of spiritual directors, parish clergy, and those in specialized ministries? How do we know when those obligations are fulfilled? Is there a difference between spiritual abuse and simple incompetence or neglect? If so, what is that difference?" "This book seeks to untangle the complex ethical responsibilities and opportunities of those whose task it is to serve as guides along the spiritual journeys of others."--Jacket.
Mapping a muddy terrain -- Spiritual care in context -- Spiritual abuse.
Includes bibliographical references (pages 161-170) and index.
Keywords: Pastoral theology; Clergy -- Professional ethics; Spiritual directors -- Professional ethics